Potential of Ramalin and Its Derivatives for the Treatment of Alzheimer’s Disease - Tai Kyoung Kim; Ju-Mi Hong; Kyung Hee Kim; Se Jong Han; Il-Chan Kim; Hyuncheol Oh; Joung Han Yim (Molecules, 2021)
The pathogenesis of Alzheimer’s disease (AD) is still unclear, and presently there is no cure for the disease that can be used for its treatment or to stop its progression. Here, we investigated the therapeutic potential of ramalin (isolated from the Antarctic lichen, Ramalina terebrata), which exhibits various physiological activities, in AD. Specifically, derivatives were synthesized based on the structure of ramalin, which has a strong antioxidant effect, BACE-1 inhibition activity, and anti-inflammatory effects. Therefore, ramalin and its derivatives exhibit activity against multiple targets associated with AD and can serve as potential therapeutic agents for the disease.